Effective Multicultural Education Strategies to Enhance Tolerance in Indonesian Schools - Amarullah, Risal Qori; Ruslandi, Ruslandi; Fadilah, Raden Muhamad Yasin; Ruswandi, Uus; Erihadiana, Mohamad (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2024)
The main problem of this research is the low awareness and understanding of the importance of multicultural education among Indonesian educators and students. The aim of this research is to identify effective multicultural education development strategies that can be implemented in Indonesian schools to increase tolerance and cultural diversity among students. This research uses a qualitative method with a literature review approach which includes in-depth analysis of literature and previous research regarding multicultural education. Data was collected by studying various journals, books and official documents that discuss the concept, implementation and impact of multicultural education. Research shows that effective strategies include integrating multicultural values into the curriculum, teacher training and development, and active participation in school community. The research concluded that implementing multicultural education in a planned and systematic manner can increase understanding and appreciation of cultural diversity, so that it can strengthen the unity and integrity of a multicultural society. Permasalahan utama penelitian ini adalah rendahnya kesadaran dan pemahaman akan pentingnya pendidikan multikultural di kalangan pendidik dan siswa Indonesia. Tujuan dari penelitian ini adalah untuk mengidentifikasi strategi pengembangan pendidikan multikultural yang efektif yang dapat diterapkan di sekolah-sekolah Indonesia untuk meningkatkan toleransi dan keragaman budaya di kalangan siswa. Penelitian ini menggunakan metode kualitatif dengan pendekatan tinjauan pustaka yang mencakup analisis mendalam terhadap literatur dan penelitian terdahulu mengenai pendidikan multikultural. Data dikumpulkan dengan mempelajari berbagai jurnal, buku, dan dokumen resmi yang membahas tentang konsep, implementasi, dan dampak pendidikan multikultural. Penelitian menunjukkan bahwa strategi yang efektif antara lain mengintegrasikan nilai-nilai multikultural ke dalam kurikulum, pelatihan dan pengembangan guru, dan partisipasi aktif dalam komunitas sekolah. Penelitian tersebut menyimpulkan bahwa penyelenggaraan pendidikan multikultural secara terencana dan sistematis dapat meningkatkan pemahaman dan apresiasi terhadap keberagaman budaya, sehingga dapat memperkuat persatuan dan kesatuan masyarakat multikultural.